Protective Immunity and Persistent Lung Sequelae in Domestic Cats after SARS-CoV-2 Infection - Chiba, Shiho; Halfmann, Peter J.; Hatta, Masato; Maemura, Tadashi; Fan, Shufang; Armbrust, Tammy; Swartley, Olivia M.; Crawford, LaTasha K.; Kawaoka, Yoshihiro (Emerging infectious diseases, 2021)
Severe acute respiratory syndrome coronavirus 2 readily transmits between domestic cats. We found that domestic cats that recover from an initial infection might be protected from reinfection. However, we found long-term persistence of inflammation and other lung lesions after infection, despite a lack of clinical symptoms and limited viral replication in the lungs.